Multimedia training package on C# programming language / Johriah Norfizlina Ismail - Johriah Norfizlina, Ismail (2002)
With the introduction of computers, many things have been digitized. The way of learning in the traditional is being replaced by computers, for example Computer Based Training (CBT) and Computer Based Education (CBE). Multimedia offers exciting and new ways to learn things and also stimulate the users' mind so that they could understand better and make learning more fun. Computers and multimedia could be the way of learning in time to come and also provide the user with a better and special environment. For my system, I intended to develop a multimedia training package on C# programming language. C# is a new language developed by Microsoft. It has a very similar syntax of Java and both have the same goal - leading the web-based language. Competition in Information Technology (IT) field nowadays is very high. That is why I chose to develop multimedia-training package on C#. By doing this, I could learn new technology at early stage. Moreover, I strongly believe that C# will be a commonly use language in future. This package combines all media features for interactivity. These elements-graphics, images, audios, videos and text, will allow me to develop a good user interface. It is best to consider on color combination, suitable music background and clear voice (explanations). This multimedia-training package acts similarly with CBT and CBE - that is in CD form. Reason - to allow easy reference and learning tools. That includes easy to carry it anywhere as long as there are an equipped of computers or laptop next to you.